The Effect of Social Media Instagram Promotion on The Sale of Mariposa Novel - Hidayatul Fajriyah; Marsudi Marsudi (Universitas Muhammadiyah Malang, 2021)
This research aims to analyze the effect of promotion on social media Instagram towards the selling of Mariposa novels. The sampling technique used in this research was the purposive sampling technique with the criteria: Mariposa novel’s sales report after being published in bookstores in 2019. In order to know the effect of social media on the selling of Mariposa novel, a statistic test namely paired sample t-test was carried out by the researcher. By dividing the sales report into two categories: sales report before the social media promotion treatment (sales report on January to June 2019) and after social media promotion treatment (sales report on July to December 2019). The result showed that the significant value was 0,028 (which is smaller than 0,05). Thus, the promotion on social media Instagram had a significant effect on the selling of Mariposa novel.